Indigenous Incarceration in Canada: A Glance at Gladue Policy - MacCarthy, Liam (Canadian Journal for the Academic Mind, 2023)
Canadian sentencing law reform in 1996 and the R. v. Gladue 1999 Supreme Court landmark decision, Canada introduced an internationally unique requirement for Canadian courts in sentencing Indigenous offenders to give special consideration to systemic factors in order to address the historic and ongoing experiences of Indigenous people in the criminal justice system Canada. While these reforms to the criminal justice system were centred around alleviating the egregious level of incarcerated Indigenous people, this analysis will reveal the implementation of Gladue principles has not been the transformative change many have hoped for. This Canadian policy research paper argues that the Canadian government’s Gladue policy has been underfunded and requires a commitment to the complete implementation of Gladue Reports and Gladue Courts to accomplish its objectives of considering the systemic circumstances of Indigenous offenders and providing criminal justice in a culturally appropriate manner.